2018
DOI: 10.4103/1319-2442.239650
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of hospital acquired acute kidney injury: A prospective study from Central India

Abstract: Acute kidney injury (AKI) is a common disorder worldwide that is associated with severe morbidity, mortality and cost. If managed adequately and in a timely manner, the majority of these cases are preventable, treatable and often reversible with simple measures. We conducted a two years prospective study of patients admitted to medical and surgical units of a tertiary care center in Central India to identify the causes of Hospital Acquired AKI (HAAKI) and its impact on patient outcomes. HAAKI occurred in 215 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
2
10
1
1
Order By: Relevance
“…All these parameters indicate that overall outcome of patients is worse in HAAKI in comparison to CAAKI. This is in accordance with that of many other studies [13,18,23]. This higher mortality may be due to multiple co-morbidities present in hospitalised patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…All these parameters indicate that overall outcome of patients is worse in HAAKI in comparison to CAAKI. This is in accordance with that of many other studies [13,18,23]. This higher mortality may be due to multiple co-morbidities present in hospitalised patients.…”
Section: Discussionsupporting
confidence: 93%
“…This variation in incidence of AKI may be as a result of the difference in standard of health care system, socioeconomic condition and educational status of the population. Males constituted the majority of patients in both the groups but there was no difference in age distribution as in a study by Goswami S et al, [13]. This male preponderance may be a reflection of the male dominating nature of our society exposing them to various environmental, occupational and social factors which can lead to AKI.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In this case-control study, we identified the clinical features of patients hospitalized for D-AKI and its associated risk factors. With the help of the ADE-ASAS-2, alarm signals were triggered in 454 cases, and 302 patients were identified as having hospital-acquired AKI; among them, 115 patients (38.08%) were diagnosed with D-AKI, consistent with the results of previous studies [ 24 , 25 ]. To include more cases and improve the sensitivity, a lenient exclusion trigger was set; the positive alarm rate was triggered in 25.33% of cases, better reflecting the real-world characteristics of D-AKI.…”
Section: Discussionsupporting
confidence: 85%